METHODS OF ORGANIZING ELECTIVE CLASSES BASED ON MULTIMEDIA TECHNOLOGIES IN VOCATIONAL EDUCATION (Conference Zone, 2022)
A non-compulsory type of training for university and high school students to expand and deepen their theoretical knowledge. Elective courses are organized on the latest issues of science, technology and culture, as well as on a topic or section that interests students (students) during the study of a subject.